Graphene: Electrochemical Production and its Energy Storage Properties - Ali, Gomaa A. M.; M. M., Yusoff; K. F., Chong (2016)
Graphene oxide was prepared by Hummers’ method and then electrochemically reduced to produce graphene nanosheets. Physicochemical characterizations were performed using XRD, FTIR, FESEM, TEM, Raman and UV–Vis techniques to elucidate the structure and morphology of the prepared material. The electrochemical studies had been conducted on graphene by cyclic voltammetry, galvanostatic charge–discharge and impedance spectra measurements, indicating its superb energy storage properties. Cyclic voltammetry show rectangular voltammograms indicating ideal electrodouble layer performance. The specific capacitance of graphene was found to be 131 F g-1 at 0.1 A g-1. Impedance spectra showed low resistance of electrochemically produced graphene, supporting its suitability for energy storage applications, such as supercapacitor.